ANALISIS HIDROMETEOROLOGI UNTUK PERENCANAAN ARTIFICIAL RECHARGE DI LAPANGAN PANAS BUMI DARAJAT - A Nurhuda , Syamsam
Water is one of supporting factor which is very important in geothermal operation power plant industry. The supplying of water is very paid attention at the Geothermal Project,while it is used for operational demanding. In this thesis research, it will take a place at the Darajat Geothermal Field in Garut, West Java. In the normal condition, water requirement for internal operation Darajat Project include requirement for two offices, project operation, water donation for Karyamekar village, shut down power plant Unit I, II, and III which is estimated average value number in 30 thousand m3/month. To fulfill the water requirement for internal operation Darajat Project which almost the majority is being supplied by two stream which locate around the Darajat Project are Cibeureum and Cipanday stream, and condensate water as a result from condensing steam at the cooling tower. The hydrometeorology analyses has been done to know the amount of surface water potention with Mock method and then analyzed probability intensity of rainfall (include the maximum probability rainfall and intensity of rainfall) which it is used for water storage in the form of artificial groundwater conservation technology (Artificial Recharge). Based on calculation, the amount of water supply potention which can be used for Darajat Project are about 7,9 million m3/year with each average water supply in the dry period is about 200 thousand m3/month and in the wet period is about 900 thousand m3/month. Furthermore, the prediction of water requirement for internal Darajat Project will increase significantly as fact as well reinjection for mass balance of reservoir management will be began at 2010, and basically it needs the amount of water as 6,7 million m3/year with each average water requirement in the dry period is about 570 thousand m3/month and in the wet period is about 550 thousand m3/month. With using Darcy Law, there is gained water debit which can be stored in the reservoir water storage as amount of 5 million m3 during wet periods at the research drainage location.